ILLUSTRATION ANALYSIS OF THE 1980s iSTi PUBLISHERS - M. Danang Syamsi; Buah Kasih Kalpitadjati; Raden Hadapiningrani Kusumohendrarto; Nofria Doni Fitri (AKSA: Jurnal Desain Komunikasi Visual, 2023)
Nowadays, history is often ignored and even forgotten, especially if the information is only written. Picture storybooks are one of the media that can be used to commemorate history. Case study in this research are the story book entitled “Ki Hajar Dewantara”, “6 Jam di Yogya”, and “Kobarkan Semangat Pertempuran” which were published by Ibu Sejati (iSTi) in the 1980s. Aspects analyzed in the form of book covers and book contents; (1) the appropriateness of the illustrations that depict important scenes in the story; (2) suitability of the depiction of the characters with the story; (3) suitability of the illustration function in the book; (4) the use of color to build certain messages and information. This research uses qualitative research supported by various data sources. The results reveal that the books fulfill all the points and are quite in accordance with storybooks that contain historical information.